(untitled) (Jurnal Manajemen dan Kewirausahaan, 2004)
The economic integration through the establishment of European Union (EU) which consists of 15 countries in January 1958 is aimed to facilitate economic collaboration and enhance the union members wealth. The last attempt of this economic integration can be seen in unifying the union member currency into EURO (although this attempt is not supported by England, Sweden, and Finland). This attempt has eventually changed the marketing stategy of many companies, excluding the countries of EU. Since they concentrate on penetrating EU’s market. The data of EU’s economic indicators show that, until the year of 2001, EU’s countries have a great market opportunity for the countries outside EU. The market opporunity is based on the fact that EU countries hold the second best GDP, after USA. With 70.74% of this GDP, it is contributed export-import activities. Besides that, the economic growth rate of EU countries is 1,5% higher than USA, and the GDP per capita is relatively high and the population of EU countries is ranked to be no.3 after China and India. As for Indonesia, the currency rate of euro which is relatively stable. Is very beneficial The EU countries that have great market opportunities to enter to are Ireland, Luxembourge, and Finland. So far there has been 10 of the EU candidates countries with good economic performance except Turkey which could enhance in the future, if they become permananet members of the union Abstract in Bahasa Indonesia : Integrasi ekonomi melalui pembentukan Uni Eropa atau Europen Union (EU) sejak Januari 1958 dengan anggota 15 negara bertujuan memudahkan kerjasama ekonomi dan peningkatan kemakmuran anggotanya. Upaya terakhir dalam pengintegrasian ekonomi adalah penyatuan mata uang EURO, walaupun tidak diikuti oleh Inggeris, Swedia, dan Finlandia. Upaya ini sekaligus merubah strategi pemasaran bagi perusahaan di negara yang tidak termasuk anggota dalam memasuki pasar EU. Berdasarkan eksplorasi data indikator ekonomi EU sampai dengan tahun 2001 terungkap bahwa negara EU merupakan tujuan pasar dengan peluang yang cukup besar bagi negara diluar anggota termasuk Indonesia yang memeliki hubungan ekonomi dengan EU. Peluang ini berdasarkarkan indikator ekonomi GDP terbesar kedua setelah Amerika Serikat, dan 70,74% dikontribusi oleh perdagangan internasional melalui kegiatan ekspor-impor, selain itu indikator pertumbuhan ekonomi 1,5% lebih tinggi dari negara Amerika Serikat, diikuti dengan angka GDP perkapita yang tinggi, populasi penduduk menduduki ukuran terbesar ketiga setelah China dan India, dan bagi Indonesia terlihat nilai tukar euro terhadap rupiah yang cukup stabil. Negara EU yang mempunyai peluang pasar lebih besar untuk dimasuki adalah Irlandi, Luxemborg, dan Finlandia. Peluang pasar ini akan meningkat lagi dimasa yang akan datang jika 10 kandidat anggota EU dengan kinerja ekonomi yang baik kecuali Turkey menjadi anggota tetap. Kata kunci: Uni Eropa, Indikator Ekonomi.